Is there an immigrant paradox in Canadian elementary students' behavioral and social adjustment?. Issue 1 (2nd January 2021) - Tardif-Grenier, Kristel; Olivier, Élizabeth; Archambault, Isabelle
ABSTRACT: The population of Canadian schools is becoming increasingly diverse in ethnic origins. Despite the challenges they face, paradox immigrant theory suggests that immigrant students have a more favorable profile than their non-immigrant peers in terms of academic success. The aim of this longitudinal study which was conducted with 66 elementary school teachers (providing information regarding 626 students from five schools located in disadvantaged areas of Montreal (Quebec, Canada) is to (1) validate whether the immigrant paradox manifests itself among elementary school children, in terms of their behavioral and social adjustment in the classroom and their educational success; and (2) study the extent to which these outcomes are associated with their educational success, differentiating whether they are first-, second-, or third-generation. Analysis of variance (ANOVA) (obj. 1) and a path analysis (obj. 2) were performed. Results show that first- and second-generation students had similar levels of hyperactivity-inattention, peer relationship difficulties, and behavioral engagement, but were advantaged in these variables as compared to their non-immigrant peers. However, none of the individual paths was significantly different among the immigration statuses. Thus, risk factors for school difficulties may not depend on the generation status of the student.